Promoting sustainable development through trade? EU trade agreements and global value chains. (30th November 2021) - Poletti, Arlo; Sicurelli, Daniela; Yildirim, Aydin B.
Abstract: Sustainable development provisions have become an integral part of the European Union's (EU's) 'new generation' trade agreements. Yet, a growing number of empirical works show that their design varies significantly, even in the trade agreements signed with countries at similar (low) levels of development. We contend that this variation can be accounted for by discussing how the growing integration of the EU economy with specific developing countries across global value chains (GVCs) affects the domestic politics of regulatory export in the EU. European firms that operate within GVCs rely on imports of inputs produced in low-labor cost countries. These firms tend to oppose the export of those regulatory burdens that generate an increase in their imports' variable costs. The political mobilization of these actors weakens domestic coalitions supporting regulatory export strategies, which explains why the EU adopts a more lenient approach over the inclusion of sustainable development provisions in Preferential Trade Agreement negotiations with some developing countries.